Early innate responses to pathogens: pattern recognition by unconventional human T-cells. (October 2015) - Liuzzi, Anna Rita; McLaren, James E; Price, David A; Eberl, Matthias
Highlights: Vγ9/Vδ2 T-cells, MAIT cells and GEM T-cells sense distinct microbial patterns. Pattern recognition occurs via biased TCRs and non-polymorphic presenting molecules. Presenting molecules include MHC-like (MR1, CD1b) and non-MHC-like (BTN3) proteins. Abstract : Although typically viewed as a feature of innate immune responses, microbial pattern recognition is increasingly acknowledged as a function of particular cells nominally categorized within the adaptive immune system. Groundbreaking research over the past three years has shown how unconventional human T-cells carrying invariant or semi-invariant TCRs that are not restricted by classical MHC molecules sense microbial compounds via entirely novel antigen presenting pathways. This review will focus on the innate-like recognition of non-self metabolites by Vγ9/Vδ2 T-cells, mucosal-associated invariant T (MAIT) cells and germline-encoded mycolyl-reactive (GEM) T-cells, with an emphasis on early immune responses in acute infection.